Tracing the trajectories of energy intensity, environmental tax revenues, and environmental neutrality in major European economies - Fayyaz Ahmad; Nabila Abid; Junaid Aftab; Aamir Javed (Energy Strategy Reviews)
Addressing the urgent challenge of climate change is a paramount global concern, with European economies showcasing commitment through the ambitious European Green Deal, COP, and sustainable development goals. However, the region's reliance on fossil fuels raises questions about the initiatives affecting the environmental neutrality goals in Europe. To find an answer to this, the present study investigates the impact of energy intensity and environmental tax revenues on environmental management efforts in terms of air, water, and waste pollution abatement in Europe by utilizing data spanning 1994 to 2020 for major European economies that held over 95 % of European economic output. The sample is grouped into two panels based on economic growth level. The study employs advanced econometric techniques to perform the preliminary checks, and GMM-PVR is used as the main study model. Aggregate panel findings reveal significant associations between energy intensity, environmental tax revenues, and environmental management. Notably, higher energy intensity is positively linked to increased environmental management activities, reflecting a commitment to address abatement goals and indicating funds are allocated toward pollution mitigation, aligning with Europe's emphasis on sustainability. Foreign direct investment has a negative relationship with environmental management. However, in Panel A, environmental tax revenues, economic growth, and trade openness reveal a negative impact on environmental management, suggesting that intense economic activities surpass the environmental tax revenue efforts to abate pollution, unlike Panel B, which is effective in pollution reduction. The study's policy implications stress enhancing the energy efficiency of economic giants while simultaneously strengthening mechanisms for utilizing environmental tax revenues and reinforcing environmental regulations to align foreign direct investment with sustainable practices. International collaboration is essential to ensure trade relations align with environmental goals, contributing to global efforts to combat climate change.